RANCANGAN BANGUN APLIKASI ABSENSI ANGKATAN DARAT BERBASIS WEBSITE : Studi: Gudang Pusat Perbekalan Angkutan Angkatan Darat - Saragih, Muhammad Daffa Arjuna Fiarnanda; Ichwani, Arief (Universitas Methodist Indonesia, 2024)
Attendance is a very important function for the employee payroll process. Calculating attendance according to the number of working days means that the listing of attendance and subsequent filing must be controlled. The Central Depot of Supplies and Transport of the Army or GUPSBEKANGAD is the central bank institution of the Indonesian armed forces headquarters, whose main mission is to provide combat logistics services and military transportation. GUPSBEKANGAD's personnel handling system is still manual, namely using attendance books and signatures. This of course affects the efficiency of data collection, data recovery and calculation of time-consuming attendance reports, so the risk of errors that lead to the loss of attendance data is getting higher. Thus, there is a requirement for an application capable of capturing attendance data and overseeing attendance reports. This research will use a prototype development methodology. It is hoped that this Army Personnel Attendance Web Application will provide convenience in the attendance process, data collection, and attendance tracking, and reduce the risk of loss and errors in listing attendance data at GPUSBEKANGAD.